Testing the unconventional; the ergonomic paddle shaft - Ewart, P. (The Engineering of sport 7, Volume 2, 2008)
The use of composite materials in sports equipment has enabled design engineers to revolutionise their products. This is seen in all sports from cycling to skiing, climbing to kayaking. Along with performance enhancement products are also being designed with ergonomic considerations that reduce athlete Stresses and support injury prevention. One aspect of product innovation seen to lag behind some radical new designs are the techniques to lest or measure the equipment performance. A product that falls into this category is the 'Crank'. The 'Crank' is an adaptation of the kayak paddle shaft which has been designed to relieve stress in the wrists and forearms of the paddler. This work investigates Standard mechanical methods used to test flexural properties of the paddle shaft and then looks at adapting this Standard to the 'Crank'. This investigation shows that use of a symmetrical loading test is not suitable given the geometry of the 'Crank'. The unsymmetrical test method proposed here in conjunction with the improved testing apparatus is proven to be suitable for use as a Standard testing regime. The test methods used here can provide mechanical data for custom shafts such as the crank and could be further developed as a tool for both performance and product benchmarking.